Environmental Science and Policy - Emily Eisenhauer; Kathleen C. Williams; Keahna Margeson; Sebastian Paczuski; Mary Clare Hano; Kate Mulvaney (Elsevier, 2025)
Increasing recognition of the complexity of environmental problems, and the need to understand social processes and human values, is leading environmental management agencies in many nations, including the USA, to integrate more research from the social sciences through the inclusion of social scientists on interdisciplinary teams. For this study we conducted focus groups at three research laboratories within the U.S. Environmental Protection Agency’s Officeof Research and Development to better understand how inclusion of social sciences influencedthe research process and outcomes, and the barriers to and facilitators of integration. The focus groups identifiedeffects on the research process including improved problem framing, the introduction of new meth- odologies, and greater stakeholder and public inclusion, while research outcomes included the inclusion or refinementof social and environmental perspectives and systems thinking, increased translatability of research, and new partnerships. Barriers identifiedincluded lack of familiarity with social sciences which affected per- ceptions of social sciences and organizational capacity to absorb and apply social science expertise. Facilitators included receptivity of team members, intentional communication strategies, and project structures and orga- nizational commitment that support interdisciplinary work. Finding a key barrier to be lack of clarity about the different roles social sciences play in translational research, we present a conceptual model definingthe roles and contributions of social scientists that clarifiesthe distinction between “integration” of social sciences in research and “application” of skills and knowledge from the social sciences which play distinct but equally important roles in translational research approaches and solutions-driven research. These insights on the ways social sciences contribute to translational research efforts advance integration of social and natural sciences in environmental science research, particularly in applied contexts.